Avaliação do impacto do programa saúde da família sobre os municípios do Rio Grande do Sul de 2005 a 2010 - Chung, Alessandra (2013)
In 1994 was implemented by the Ministry of Health the Family Healthcare Program (PSF), with the goal of providing assistance to families and / or registered persons, in order to promote better living conditions. In 2005, 4.986 municipalities had adopted the program. In the following years, this number has increased and in 2010 the number of municipalities that had implemented the program was 5.294. This paper analyzes the impact of the Family Healthcare Program on infant mortality in cities with over 50.000 inhabitants in the state of Rio Grande do Sul for the years 2005-2010. Using the methodology of panel data, it was found that the population coverage of the PSF, analyzed individually, did not produce the expected results, was not effective in reducing child mortality in the municipalities of Rio Grande do Sul. However, considering it in conjunction with the Community Health Agents program (PACS) and lagged in one period, the results were significant in reducing child mortality. It can be concluded, therefore, that programs are complementary and influence the decline of infant mortality, and this effect occurs from a certain time interval.